Reflexiones acerca del estudio del perfil psicopatológico de la mujer adicta-maltratada - Mercado Justiniano, Gloriam Zaid (Archivos de criminología, seguridad privada y criminalística, 2020)
The objective of this study is to reflect on the addicted-abused woman, questioning some positions that exist and taking the main ideas to carry out a constructive criticism from the Puerto Rican situation. It concludes with a series of recommendations in relation to women's social problems, especially with a focus on the stigma that they suffer